Disabilities and trends over time in a French county, 1980–91. Issue 2 (1st February 2003) - Cans, C; Guillem, P; Fauconnier, J; Rambaud, P; Jouk, P S
Abstract : Aim: To describe trends over time and types of disability for children born in a French county from 1980 to 1991. Methods : Data were collected from medical records of a morbidity register; disabled children with at least one severe deficiency have been included. Prevalence rates are given per 1000 resident children, over four three-year periods. Results : Overall, 7.73 per 1000 children (that is, 1360 children), had a severe childhood disability, and the prevalence rate had increased significantly since 1980. This increase was mainly owing to an increase in cerebral palsy and psychiatric disorder prevalence rates. Conclusion : Future research aimed to explain these trends over time can be based on such data. The present knowledge is useful for planning purposes.